ANALISIS KONVERSI LAHAN PERTANIAN SAWAH DI KECAMATAN KURANJI KOTA PADANG - Azzahra, Umiyatul; Iskarni, Paus (DEPARTEMEN GEOGRAFI FIS UNP, 2025)
Land conversion is the process of transitioning land use from one form of use to another. The objectives of this research are: 1) The area of rice field conversion, 2) The conversion of rice field land cover, 3) Factors causing the conversion of rice fields, and 4) The distribution pattern of rice field conversion. This research uses Mixed Methods, combining two forms of research approaches, namely quantitative and qualitative. Data analysis uses Landsat 8 images for 2013, 2018 and 2022 with overlay analysis techniques and Nearest Neighbor Analysis (ANN). The results of the research, 1) The decrease in the area of rice fields also causes a reduction in the conversion of rice fields covering an area of 930.95 ha in 2013-2022. 2) The conversion of paddy land cover is divided into 2 types of paddy land cover, namely built-up land covering an area of 678.30 ha and mixed agriculture covering an area of 137.39 ha. 3) The factors causing the conversion of rice fields in Kuranji District are due to increasing population growth, economic pressure, and damage to irrigation for irrigating rice fields. 4) Results The 2013-2022 land conversion distribution pattern produces a clustered pattern type.